Plant architecture and meristem dynamics as the mechanisms determining the diversity of gall-inducing insects - Espírito-Santo, Mário M; de S. Neves, Frederico; Andrade-Neto, Francisco R; Fernandes, G. Wilson (Oecologia, 2007)
Plant architecture is considered to affect herbivory intensity, but it is one of the least studied factors in plant-insect interactions, especially for gall-inducing insects. This study aimed to investigate the influence of plant architecture on the speciose fauna of gall-inducing insects associated with 17 species of Baccharis. Five architectural variables were evaluated: plant height, number of fourth-level shoots, biomass, average level and number of ramifications. The number of galling species associated with each host plant species was also determined. To test the effects of plant architecture on gall richness at the individual level, we used another data set where the number of fourth-level shoots and gall richness were determined for B. concinna, B. dracunculifolia, and B. ramosissima every 3 weeks during 1 year. The average similarity between host species based on gall fauna was low (9%), but plants with the same architectural pattern tended to support similar gall communities. The most important architectural trait influencing gall richness at the species level was the number of fourth-level shoots, which is indicative of the availability of plant meristems, a fundamental tissue for gall induction and development. This variable also showed a positive correlation with gall richness at the individual level. We propose that variations in gall richness among host species are driven by interspecific differences in plant architecture via availability of young, undifferentiated tissue, which is genetically controlled by the strength of the apical dominance. Plant architecture should have evolutionary consequences for gall communities, promoting insect radiation among architecturally similar plants through host shift and sympatric speciation. We also discuss the role of plant architecture in the global biogeography of gall-inducing insects.